Implementation of the Canva-Assisted Project-Based Learning Model to Improve Students' Creative Thinking in the Aqidah Akhlak Subject at MTs Al-Amin, Jenu District - Wahyu Isnatur Rohmah (Manajia: Journal of Education and Management, 2026)
Creative thinking skills are essential in twenty-first century learning to enable students to respond effectively to complex challenges, including in Aqidah Akhlak education which emphasizes character development. However, learning practices in schools are still largely dominated by teacher-centered approaches that limit students’ active participation and creativity. This study aims to examine the implementation of Project-Based Learning (PjBL) supported by the Canva application in improving students’ creative thinking skills in Aqidah Akhlak learning at MTs Al-Amin, Jenu District. The research employed a qualitative approach using Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection. Data were collected through observation, interviews, and documentation, and analyzed using descriptive qualitative analysis. The findings indicate a significant improvement in students’ engagement, creativity, and learning outcomes. In the pre-cycle stage, student participation and achievement were relatively low, whereas after the implementation of PjBL assisted by Canva in the second cycle, student participation increased to approximately 80% and learning mastery reached 82%. Students demonstrated the ability to generate more original, flexible, and contextually relevant ideas. The study concludes that Project-Based Learning supported by Canva is effective in enhancing creative thinking skills and improving the quality of Aqidah Akhlak learning.